Pengaruh Unggahan Foto Di Instagram Terhadap Minat Kunjungan Di M Bloc Space Jakarta - Putrasatia, Rahman; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA, 2022)
The activity of uploading photos to Instagram is an activity that has often been carried out by most Jakarta residents who have smart phones. Uploading photos creates the effect of interest in this digital era, because almost everything is done digitally. The research aims to see whether there is an effect of uploading photos on the Instagram on interest in visits. This research uses two data namely primary and secondary data. The data collection techniques in this research use observation, documents, and questionnaires. The analysis technique for this research is a questionnaire test, namely validity and reliability testing, hypothesis testing, namely the t test, and statistical analysis, namely analysis. correlation analysis and linear regression. The results of the research are to see what types of photo uploads people like about M Bloc Space Jakarta and see whether there is an effect of uploading photos on Instagram on interest in visits. The most liked photo uploads about M Bloc Space Jakarta are those about architecture or building style. There is an effect of uploading photos on Instagram on interest in visiting M Bloc Space Jakarta Keyword: Photo upload effect, Interest in visiting, M Bloc Space Jakarta